Sustainability in the Food and Beverage Industry: A Comparative Study of Malaysia, India, and Indonesia - Kee, Daisy Mui Hung; Lee, Jerome Vui Khiong; Binti Azlan, Izza Yasmin Adriana; Subramaniam, Jeevasriirubini A/P; Koay, Jocelyn Chia Wen; Putri, Ayu Melissa; Asthana, Ritanshi; Shrivastava, Kshitiz; Beg, Ashiza (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
This study presents a comparative study on sustainability practices in the food and beverage (FB) industry of three Southeast Asian countries: Malaysia, India, and Indonesia. Sustainability in the FB industry of a country has gained wide concern due to the growing environmental, social and economic impact. This study aims to examine whether the consumers’ awareness and knowledge and consumers’ attitudes will influence the sustainability practices implemented by three different countries as well as to compare the sustainable practices in the FB industry across countries. Data was collected through a Google Forms survey with a sample size of 150 respondents. This paper will also study the other factors contributing to the implementation of sustainability practices in Malaysia, India and Indonesia. The findings of this study revealed that the consumers’ awareness and knowledge, attitude and other factors contributing to sustainability are collectively mediated by the implementation and promotion of sustainable practices in the FB industry. However, adopting sustainable practices varies across countries due to the complex relationship of those variables.